Checklist of decapods (Crustacea) from the coast of São Paulo State (Brazil) supported by integrative molecular and morphological data: II. Infraorder Caridea: Family Alpheidae - Almeida, Alexandre O.; Terossi, Mariana; Buranelli, Raquel C.; Castilho, Antonio L. [UNESP]; Costa, Rogério C. [UNESP]; Zara, Fernando J. [UNESP]; Mantelatto, Fernando L. (Magnolia Press, 2018)
This study is part of a series of checklists resulting from a long-term multidisciplinary project on the biodiversity of decapod crustaceans from the marine and coastal environments (including estuaries) of São Paulo State (Brazil). For that, we integrated molecular techniques (mitochondrial DNA markers) and morphological analyses of adult specimens for an accurate and detailed identification. The DNA markers were used when the morphological identification was doubtful, particularly in the recognition of cryptic species. This second manuscript presents a checklist of the Alpheidae caridean shrimps from the coast of São Paulo. We report the occurrence of Alpheus cf. paracrinitus and Synalpheus townsendi for the first time in the region. Based on our survey, 39 species of Alpheidae are known for this region: Alpheus (21 spp.), Athanas (2 spp.), Automate (2 spp.), Leptalpheus (1 spp.), Salmoneus (3 spp.), and Synalpheus (10 spp.). We collected 28 species and obtained cytochrome oxidase subunit I (barcode region) and/or 16S partial sequences of 26 of them. These sequences may be used for phylogenetic and populational analyses in further studies.
Keywords: 16Smt; Biodiversity; COI; Distribution; Marine shrimps